Pelatihan Layanan Bimbingan Karir Bagi Santri Dan Ustadzah Dalam Meningkatkan Motivasi Melanjutkan Ke Perguruan Tinggi Di Pondok Pesantren Mathla’ul Anwar Karyabakti – Kecamatan Batu Jaya – Kabupaten Karawang - Fahmi, Ilham; Faizin, Muhamad; Abubakar; Fathurrohman, N.; Karifal, Muhamad; Septiyani, Wellina Dian (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
Pesantren is an institution that serves as a platform for the younger generation to gain knowledge, particularly Islamic religious education. Santri, as the golden generation of the future, must be equipped with strong religious knowledge for their afterlife while also being motivated to pursue higher education as a preparation for their careers in today's complex and highly competitive global world. This program aims to enhance the motivation of santri at Pesantren Mathla'ul Anwar Karyabakti, Karawang Regency, to pursue higher education. Pesantren is chosen as the implementation site because it is where many santri live and learn, thus ensuring a significant impact on the target group. The implementation steps include organizing training for the Career Guidance Service Program, specifically designed to meet the needs of santri. The training materials cover concepts of career guidance services, career planning, motivation for further studies in higher education, and opportunities and challenges in the development of science and technology in the future. Additionally, practical applications such as case studies or simulations are also included. Through this program, santri are expected to enhance their understanding of career guidance services, enabling them to make more informed and responsible career planning decisions. Moreover, increasing the motivation to pursue higher education is expected to help santri plan better career directions for the future. The implementation of this PKM program is designed holistically and systematically to achieve clear and measurable career direction goals for the santri. Program evaluation is conducted to assess the level of understanding and behavioral changes among the santri after participating in the training. Feedback collection from participants and pesantren management is also involved to continually improve the program's quality. Thus, this PKM program is capable of making a positive contribution to enhancing the motivation of santri to continue to higher education, enabling them to be better prepared to face technological challenges and empower themselves in the future. Conclusion The training revealed that many santri have not yet determined their future careers or have a clear picture of the higher education pathways to pursue. This training serves as both motivation and socialization about the importance of determining future career directions for santri. Outputs of this community service program include a scientific article published in a nationally indexed Sinta journal, an activity video, a printed mass media article, and relevant intellectual property products (HKI).